Insect and mite pests diversity in the oilseed crops ecosystems in Bangladesh (Bangladesh Journal of Zoology, 2012)
No abstract available.DOI: http://dx.doi.org/10.3329/bjz.v39i2.10594 Bangladesh J. Zool. 39(2): 235-244, 2011